The IK1/Kir2.1 channel agonist zacopride prevents and cures acute ischemic arrhythmias in the rat - Zhai, Xu-Wen; Zhang, Li; Guo, Yun-Fei; Yang, Ying; Wang, Dong-Ming; Zhang, Yan; Li, Pan; Niu, Yi-Fan; Feng, Qi-Long; Wu, Bo-Wei; Cao, Ji-Min; Liu, Qing-Hua (PLOS ONE, 2017)
Arrhythmogenesis in acute myocardial infarction (MI) is associated with depolarization of resting membraine potential (RMP) and decrease of inward rectifier potassium current (IK1) in cardiomyocytes. However, clinical anti-arrhythmic agents that primarily act on RMP by enhancing the IK1 channel are not currently available. We hypothesized that zacopride, a selective and moderate agonist of the IK1/Kir2.1 channels, prevents and cures acute ischemic arrhythmias. To test this viewpoint, adult Sprague-Dawley (SD) rats were subjected to MI by ligating the left main coronary artery. The antiarrhythmic effects of zacopride (i.v. infusion) were observed in the settings of pre-treatment (zacopride given 3 min prior to coronary occlusion), post-treatment (zacopride given 3 min after coronary occlusion) and therapeutic treatment (zacopride given 30 s after the onset of the first sustained ventricular tachycardia (VT)/ventricular fibrillation (VF) post MI). In all the three treatment modes, zacopride (15 μg/kg) inhibited MI-induced ventricular tachyarrhythmias, as shown by significant decreases in the premature ventricular contraction (PVC) and the duration and incidence of VT or VF. In Langendorff perfused rat hearts, the antiarrhythmic effect of 1 μmol/L zacopride were reversed by 1 μmol/L BaCl2, a blocker of IK1 channel. Patch clamp results in freshly isolated rat ventricular myocytes indicated that zacopride activated the IK1 channel and thereby reversed hypoxia-induced RMP depolarization and action potential duration (APD) prolongation. In addition, zacopride (1 μmol/L) suppressed hypoxia- or isoproterenol- induced delayed afterdepolarizations (DADs). In Kir2.x transfected Chinese hamster ovary (CHO) cells, zacopride activated the Kir2.1 homomeric channel but not the Kir2.2 or Kir2.3 channels. These results support our hypothesis that moderately enhancing IK1/Kir2.1 currents as by zacopride rescues ischemia- and hypoxia- induced RMP depolarization, and thereby prevents and cures acute ischemic arrhythmias. This study brings a new viewpoint to antiarrhythmic theories and provides a promising target for the treatment of acute ischemic arrhythmias.